New Technologies of Internet Employment: Reducing Costs With an Economic Value Model - Yami, Shirin (European Scientific Journal, ESJ, 2022)
This paper focuses on examining the effect of applying the classical model of the economic value of the order on the employment activities of human resources in an organization. Initially, based on the classical model, the economic value of the order is modeled and the value of unique costs of employment activities such as human resource management and related coordination is obtained. Thereafter, the status in the two cases before and after the implementation of this technology is compared and this situation is analyzed by providing a numerical example. The optimal costs of investment are increasing rapidly. On the other hand, the development of efficient technologies in the employment system has caused the total number of employees to be hired to always be higher than the minimum required level set in this model. Investment in this area has declined. The result shows that with the implementation of this technology, due to the reduction of existing costs, on the one hand, the economic value of order decreases and on the other hand increases the total optimal profit.